Esensi Dan Urgensi Nilai-Nilai Spiritual Islam Dalam Pembangunan Bangsa Indonesia - Nurhilaliyah (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This research examines the essence and urgency of Islamic spiritual values within the context of Indonesian nation-building. As a country with a Muslim majority, Indonesia holds significant potential to integrate the noble tenets of Islamic teachings—such as Tawhid (monoteis), Ukhuwah (brotherhood), 'Adl (justice), Amanah (trustworthiness), and tolerance—as the moral and ethical foundation for national development. The spiritual essence of Islam focuses not merely on ritual dimensions but also on shaping individualis with integrity, responsibility, and social concern. The urgency of these values lies in their role as an antidote to various developmental challenges, including corruption, social disintegration, economic disparity, and moral crisis. By internalizing spiritual values, it is expected that a harmonious, just, and prosperous society will be created, alongside a clean and authoritative state administrator. This study concludes that the mainstreaming of Islamic spiritual values through education, public policy, and the active role of religious institutions is a pressing and strategic necessity to achieve sustainable and dignified nation-building, in line with the ideals of Pancasila and the 1945 Constitution.